2018
DOI: 10.3390/agronomy8100223
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Soil-Applied Fungicides on Sugarcane Root and Shoot Growth, Rhizosphere Microbial Communities, and Nutrient Uptake

Abstract: Sugarcane (Saccharum spp. hybrid) successive planting (also called monoculture) causes serious yield losses and its management is not well studied in Histosols. Based on very few studies in other sugarcane regions, root colonization by harmful soil fungi is considered as a major cause of this yield decline, but there is lack of knowledge on its management in Histosols. A two-year greenhouse study was conducted with soil-drench application of mancozeb, mefenoxam, and azoxystrobin fungicides to determine their e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 39 publications
2
16
0
Order By: Relevance
“…These authors demonstrated under similar in vitro culture conditions that azoxystrobin at 0.1 mg L −1 (as formulation Amistar) affected spore production and hyphal length of R. irregularis MUCL 41833 associated with potato, while root colonization was reduced at 1 (a.i., or formulation Amistar) and 10 mg L −1 a.i. Greenhouse studies further demonstrated that soil drench with azoxystrobin inhibited root colonization of Glomeraceae members in sugarcane (Vuyyuru et al, 2018). Moreover, root colonization and enzymatic activity of Funneliformis coronatum associated with maize plants was also inhibited, demonstrating the fungicidal activity of this strobilurin, probably on the respiratory electron transfer within mitochondria, where succinate dehydrogenase is part of complex II (Diedhiou et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…These authors demonstrated under similar in vitro culture conditions that azoxystrobin at 0.1 mg L −1 (as formulation Amistar) affected spore production and hyphal length of R. irregularis MUCL 41833 associated with potato, while root colonization was reduced at 1 (a.i., or formulation Amistar) and 10 mg L −1 a.i. Greenhouse studies further demonstrated that soil drench with azoxystrobin inhibited root colonization of Glomeraceae members in sugarcane (Vuyyuru et al, 2018). Moreover, root colonization and enzymatic activity of Funneliformis coronatum associated with maize plants was also inhibited, demonstrating the fungicidal activity of this strobilurin, probably on the respiratory electron transfer within mitochondria, where succinate dehydrogenase is part of complex II (Diedhiou et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…(2015) . Though soil application of azoxystrobin inhibited root colonization of Glomeraceae members ( Vuyyuru et al., 2018 ), foliar application of azoxystrobin not affect AM root colonization ( Campos et al., 2015 ). Benomyl, Bavistin, Captan and Mancozeb were tested on association of R. fasciculatus with Panicum miliaceum L.The results of this study showed significant ( P ≤ 0.05) higher AM colonization, spore density, plant growth and grain yield treated with Captan compared to other fungicides and untreated controls.…”
Section: Hindrances To Utilize Amf In Agriculturementioning
confidence: 99%
“…(2015) . Though soil application of Azoxystrobin inhibited root colonization of Glomeraceae members, foliar application is safe ( Vuyyuru et al., 2018 ). Alternative use of similar less harmful fungicides or low doses may be practiced.…”
Section: Way Out To Utilize Am In Agriculturementioning
confidence: 99%
“…The treatments were: (i) Untreated, (ii) Mancozeb 2.5 kg a.i ha −1 (Manzate Max ® , United Phosphorus Inc., King of Prussia, PA, USA), iii) Mefenoxam, 0.57 kg a.i ha −1 (Ridomil Gold ® 2E, Syngenta Corporation, Greensboro, NC, USA), and (iv) Azoxystrobin, 0.3 kg a.i ha −1 (Quadris ® 2.08SC, Syngenta Corporation, Greensboro, NC, USA). Further description of commercial formulations of these fungicides can be found in Vuyyuru et al [29]. Fungicides were topically applied as a 15 cm concentrated band over seed cane pieces in the furrows prior to covering with soil.…”
Section: Fungicide Treatmentsmentioning
confidence: 99%
“…An alternate method, such as dipping the sets in a fungicidal solution, may be a better choice [12]. This may be the reason that mancozeb caused a significant improvement in sugarcane root and shoot growth in a greenhouse study [29] where the soil was drenched with a fungicide solution. In high organic matter soils, azoxystrobin was reported to be degraded faster by soil microbial communities [53], and greater response with mefenoxam may be due to its more systemic and persistent nature.…”
Section: Fungicidal Effects On Sugarcane Tiller Dynamics and Crop Yieldsmentioning
confidence: 99%